2014
DOI: 10.1161/hypertensionaha.114.03394
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bona Fide Alternative Renin Transcripts Expressed Along Cortical Tubules and Potential Roles in Promoting Insulin Resistance In Vivo Without Significant Plasma Renin Activity Elevation

Abstract: Abstract-Renin belongs to a family of aspartyl proteases and is the rate-limiting enzyme in the synthesis of the potent vasoactive peptide angiotensin II. Processing of renal renin has been extensively investigated in juxtaglomerular granular cells, in which prorenin and active renin are present in secretory condensed granules. Previous studies demonstrated alternative renin transcription in rat adrenal glands. Different studies reported novel intracellular forms of renin deduced from novel 5′ variants derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…A second source of renal renin is the collecting duct cells that secrete active renin into the tubular fluid (52,71,82,92,113). There is evidence for alternative gene products of intracellular renin in the kidney, brain, and adrenal that may imply a renin-dependent pathway for the intracellular expression of angiotensin peptides (65,76,106,107,142). Apart from its catalytic activity, prorenin may constitute an additional circulating hormone of the RAS through binding and activation of the prorenin receptor within various tissues (52,71,94).…”
Section: Ras Protein Componentsmentioning
confidence: 99%
“…A second source of renal renin is the collecting duct cells that secrete active renin into the tubular fluid (52,71,82,92,113). There is evidence for alternative gene products of intracellular renin in the kidney, brain, and adrenal that may imply a renin-dependent pathway for the intracellular expression of angiotensin peptides (65,76,106,107,142). Apart from its catalytic activity, prorenin may constitute an additional circulating hormone of the RAS through binding and activation of the prorenin receptor within various tissues (52,71,94).…”
Section: Ras Protein Componentsmentioning
confidence: 99%
“…Renin activity as measured by aliskerin-sensitive inhibition of Ang I formation from angiotensinogen was also evident in isolated nuclei in the renal epithelial NRK-52 cells, as well as quantifiable levels of Ang I, Ang II, and Ang-(1-7) [22]. In confirmation of intracellular renin within the kidney, Ishigami and colleagues report a truncated renin transcript expressed in the proximal tubules of the mouse kidney [16]. Overexpression of the renin isoform within the proximal tubules was associated with a sustained elevation in blood pressure and no change in the circulating levels of renin [16].…”
Section: Reninmentioning
confidence: 88%
“…In confirmation of intracellular renin within the kidney, Ishigami and colleagues report a truncated renin transcript expressed in the proximal tubules of the mouse kidney [16]. Overexpression of the renin isoform within the proximal tubules was associated with a sustained elevation in blood pressure and no change in the circulating levels of renin [16]. Although the intracellular distribution of the renin isoform was not ascertained, the fact that overexpression of tubular renin augmented blood pressure is consistent with previous studies demonstrating that the increased expression of proximal tubule angiotensinogen, the AT 1 R, or intracellular Ang II also resulted in a sustained increase in blood pressure [23][24][25][26][27][28].…”
Section: Reninmentioning
confidence: 98%
See 1 more Smart Citation
“…47 In the kidney, a truncated intracellular renin isoform has been identified in collecting ducts and generates local angiotensin II, leading to inflammation and systemic insulin resistance without an elevation in plasma renin. 47 After localizing renin mRNA in the kidney, 48 we showed that stimuli known to affect renin secretion had similar effects on renal renin mRNA levels. [49][50][51][52] Perturbations in renin mRNA were then documented in the kidney and other tissues in models of hypertension.…”
Section: Prorenin Renin Biosynthetic Pathway Renin Gene Isolation mentioning
confidence: 99%